2017
DOI: 10.5897/ijbc2016.1101
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and morphological characterization of Musa spp. in North Kivu and Ituri provinces, Eastern Democratic Republic of Congo

Abstract: Eastern Democratic Republic of Congo constitutes an area where the East African Highland bananas (Musa-AAA-EA) and plantains (Musa-AAB) meet. However, Musa diversity in this region has never been characterized nor represented in national or international collections, yet increasing human activities and build-up of pests and diseases, especially Xanthomonas wilt of banana and banana bunchy top disease, could negatively affect this diversity. This study assessed, collected and morphologically characterized on-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…Subject to molecular characterization to elucidate this synonymy, it is clear that clusters 2 and 4 (Figure 4 and Table 2) included more accessions with names varying very little between sociolinguistic groups. These results are similar to that of the work by Sivirihauma et al (2017b) in Ituri (DRC) where 14.4% French type, 44.5% False horn and 0.5% True horn were recorded in a collection.…”
Section: Main Discriminating Characters Of Plantainssupporting
confidence: 90%
See 1 more Smart Citation
“…Subject to molecular characterization to elucidate this synonymy, it is clear that clusters 2 and 4 (Figure 4 and Table 2) included more accessions with names varying very little between sociolinguistic groups. These results are similar to that of the work by Sivirihauma et al (2017b) in Ituri (DRC) where 14.4% French type, 44.5% False horn and 0.5% True horn were recorded in a collection.…”
Section: Main Discriminating Characters Of Plantainssupporting
confidence: 90%
“…In fact, morphological traits have been used over the past 70 years in the study of Musa diversity (Adheka et al, 2018). Several studies carried out on agro-morphological characterization have successfully classified plantain cultivars in several countries (Amoutchi et al, 2020;Batte et al, 2018;Sivirihauma, et al, 2017b). Those studies indicated that a wide range of morphological traits could be a relevant tool for germplasm identification and selection.…”
Section: Introductionmentioning
confidence: 99%
“…Field experiments were established in September 2010 at the Catholic University of Graben's (UCG) regional Musa germplasm collection at Butembo (1815 m a.s.l., 00.11786° N, 29.2587° E) in North Kivu province, for assessment of plantain cultivar yield and pro‐vitamin A content. Butembo has sandy clay soils with pH 5.7, 5.1% organic carbon (OC), 0.26% nitrogen, 10.6 mg kg −1 of available phosphorus and 1.14 cmol(+) kg −1 of potassium . The site had a mean annual rainfall of 1036 mm and a mean annual temperature of 19 °C.…”
Section: Methodsmentioning
confidence: 99%
“…28,49,50 This region also has a high variability in its soils, including volcanic soils, alluvial soils, naturally weathered deep and humus-rich rock soils. 28 This study was conducted on 48 different local plantain cultivars (AAB), previously collected through a Musa germplasm survey covering three districts in North Kivu province and five in Ituri province of eastern DR Congo ( Table 2, 51 ). It is estimated that the plantains used in this study represent about 30% of the known plantain diversity across DR Congo.…”
Section: Study Region and Plantain Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation